(untitled) (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2026)
In this article, the authors present a pilot industrial version of a flat solar water heating collector. This collector is equipped with reflectors and twisted channel absorber tubes, and is integrated with paraffin as a phase change material (PCM). The authors also conducted an experimental study of the collector’s energy efficiency. These studies took place in July and August 2025 at the “Alternative Energy Sources” training and scientific polygon of Karshi State Technical University, in conditions representative of the region’s natural meteorological and climatic conditions. During these studies, changes in solar radiation, outdoor air temperature and water temperature at the collector outlet were measured, and the results were analysed. Data on solar radiation was recorded using the NASA POWER and GIDROMET databases, as well as measuring and control devices installed during the research. The results showed a consistent increase in water temperature with increasing solar radiation, which accelerated heat exchange processes significantly due to the reflectors and twisted channel tubes. Notably, despite the decrease in solar radiation after 16:00, the water temperature remained high for a period, indicating the release of heat accumulated by the paraffin-based FCM during the day.